1995
DOI: 10.1103/physrevlett.74.2941
|View full text |Cite
|
Sign up to set email alerts
|

Optical Soliton Propagation in an Erbium Doped Nonlinear Light Guide with Higher Order Dispersion

Abstract: We propose a coupled system of the Hirota equation and the Maxwell-Bloch equations to describe the wave propagation in an erbium doped nonlinear fiber with higher order dispersion.The Painleve property of the same is analyzed and the coupled system is found to be integrable. The Lax pair is also constructed and the single-soliton solution is explicitly shown. The coupled system is found to allow soliton-type propagation. PACS numbers: 42.SO.Rh, 02.30.Jr, 42.65. -k, 42.81.DpThe extraordinary growth of communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
73
0
4

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 14 publications
0
73
0
4
Order By: Relevance
“…Recent experiments by Nakazawa et al, have confirmed guided wave SIT soliton formation and propagation by employing a few meters of erbium doped fibre [8][9][10][11]. Recently, considering all higher order effects in the propagation of femtosecond pulses, the coupled Hirota and Maxwell-Bloch (CH-MB) equations have been proposed and analyzed for soliton solutions [12]. Some generalization of NLS-MB equations, for instance, the CH-MB equations and the NLS-MB equations with variable dispersion and nonlinear effects are discussed [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent experiments by Nakazawa et al, have confirmed guided wave SIT soliton formation and propagation by employing a few meters of erbium doped fibre [8][9][10][11]. Recently, considering all higher order effects in the propagation of femtosecond pulses, the coupled Hirota and Maxwell-Bloch (CH-MB) equations have been proposed and analyzed for soliton solutions [12]. Some generalization of NLS-MB equations, for instance, the CH-MB equations and the NLS-MB equations with variable dispersion and nonlinear effects are discussed [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…(24) into eqs. (11,12,13), we can get the first order rogue waves {Ē [1] ,p [1] ,η [1] } in the form of determinant. The dynamical evolution of |Ē [1] | 2 , |p [1] | 2 andη [1] for the parametric choice Theorem 2.…”
Section: The Higher Order Rogue Waves and Their Determinant Formsmentioning
confidence: 99%
“…We consider ultrashort pulses propagating a resonant erbium-doped fiber system with the important higherorder effects above governed by a coupled system of the H-MB model [5] …”
Section: The H-mb System and Exact Multi-peak Soliton Solutionmentioning
confidence: 99%
“…In this case, nonlinear wave propagation could possess both the effects due to a mix of silica and erbium impurities. More specifically, the silica material gives the group velocity dispersion and self-phase modulation effects, which is governed by the nonlinear Schrödinger (NLS) equation; whereas Er impurities contribute to the self-induced transparency (SIT), which is described by the Maxwell-Bloch (MB) model [1][2][3][4][5][6][7][8][9]. As a result, the constraint to the NLS soliton namely the optical losses can be somewhat compensated with the effect of SIT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation